Building biocultural approaches into Aotearoa – New Zealand's conservation future. Issue 3 (3rd July 2019) - Lyver, Phil O'B.; Ruru, Jacinta; Scott, Nigel; Tylianakis, Jason M.; Arnold, Jason; Malinen, Sanna K.; Bataille, Corinne Y.; Herse, Mark R.; Jones, Christopher J.; Gormley, Andrew M.; Peltzer, Duane A.; Taura, Yvonne; et al.
ABSTRACT: Indigenous peoples' roles in conservation are important because they offer alternate perspectives and knowledge centred on the quality of the human–environment relationship. Here, we present examples of Māori cultural constructs, mechanisms, legislative warrants and customary (traditional and contemporary) interventions fundamental to the development and delivery of biocultural approaches within NZ's future conservation system. Biocultural approaches emphasise greater decision-making for the environment at the local institutional level, and contribute towards rebuilding a 'tuakana–teina' relationship (a reciprocal learning relationship and responsibility shared between older and younger persons) between societies and their environments. We further posit that the matching of social scales with ecological scales within local management is necessary for the effective implementation of biocultural approaches. Failure to do so could undermine motivation, action, energies and confidence of local communities.